Effects of policy reforms on firm innovation - Murat Şeker; Mehmet Fatih Ulu (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
The regulatory environment in a country is an important factor that affects firm performance. This study investigates the impact of a particular regulation - license requirements for certain firm activities - on the innovation performance of Indian firms in the 1990s. Using a unique firm-level panel data set, it shows that the removal of license requirements led to an eight percentage points higher innovation rate within two years following the reform. We measure innovation as the introduction of new product varieties that had not been produced by the firm before. It takes a longer time for firms to innovate in industries in which they were not producing before. The conclusions in this study are also robust to the inclusion of controls for other policy reforms that occurred during the period of licensing reform. They also persist in tests with different subgroups of firms and with the use of alternative estimation methods.
Keywords: L11; L52; O14; O31; O38; 330; Innovation; research and development; regulatory environment; regulations; industrial policy; India